Islamic Education And Family Extremism In Indonesia: Critical Pedagogy In Conservative Family Muslim Education - Badrun (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This article aimed to examine how Islamic education was taught in Muslim families and to what extent education in those families supported extremism, one suspected of involvement in some religious extremist cases in Indonesia. Considering the participation of all family members, such as husbands, wives, and children, simultaneously in some suicide bombing cases, it is essential to examine parental education levels, roles, and functions in such families. This study highlights the shift in the traditional role of wives, who were previously underappreciated but now play a significant role in shaping the family's religious beliefs. The primary focus of the study is to examine how families can become a means of spreading extremist ideologies. The study gathered data through a literature review and in-depth interviews with families suspected of involvement in extremist activities in Indonesia. The findings showed that families could serve as a conduit for the propagation and dissemination of extremism, with women, particularly wives, and children, occasionally being susceptible to indoctrination under the guise of education. In contrast, at other times, wives act as agents responsible for transmitting extremist ideologies.